Clinical importance of HIV and depressive symptoms among veterans with HIV infection. - Kilbourne, Amy M; Justice, Amy C; Rollman, Bruce L; McGinnis, Kathleen A; Rabeneck, Linda; Weissman, Sharon; Smola, Susan; Schultz, Richard; Whittle, Jeff; Rodriguez-Barradas, Maria (Journal of general internal medicine, 2002)
To compare the clinical importance (association with illness severity and survival) of depressive and HIV symptoms among veterans with HIV infection.
Keywords: Adult; CD4 Lymphocyte Count; Comorbidity; Cross-Sectional Studies; Depression; Female; HIV Infections; Humans; Male; Middle Aged; Proportional Hazards Models; Severity of Illness Index; Survival Analysis; United States; Veterans; Viral Load